Family screening in dilated cardiomyopathy-qualifying screening and need for follow-up. (3rd October 2022) - Vissing, C R; Espersen, K; Mills, H L; Bartels, E D; Jurlander, R; Skriver, S V; Ghouse, J; Thune, J J; Axelsson Raja, A; Christensen, A H; Bundgaard, H
Abstract: Background: Guidelines recommend family screening in dilated cardiomyopathy to uncover pre-symptomatic disease to improve morbidity and mortality through early treatment. According to patterns of inheritance and incomplete penetrance, less than half of relatives to dilated cardiomyopathy probands will develop disease, but so far, no guidelines provide recommendations on the frequency and intensity of follow-up screening. Purpose: To investigate the prevalence and incidence and identify predictors of developing familial dilated cardiomyopathy (FDC) in relatives participating in family screening. Methods: The study was an observational, longitudinal cohort study of families screened and followed from 2006 to 2020, at a regional assembly of clinics for inherited cardiomyopathies in Denmark. Results: We included 211 families totaling 774 subjects (n=563 relatives, 47% women). At baseline, 124 relatives (22%) were diagnosed with dilated cardiomyopathy, while 43 relatives (8%) not fulfilling FDC criteria were found to carry class IV to V genetic variants. Thus, the combined clinical and genetic yield of screening was 30% at baseline. Relatives not fulfilling diagnostic criteria for FDC at baseline (n=439), were stratified into four groups based on results from genetic screening and clinical work-up at baseline (Figure 1). The risk of developing FDC during follow-up was strongly associated with this classification (see figure 1 and 2). The highest risk of developing FDC was observed in relatives carrying class IV to V genetic variants (n=43, age-adjusted incidence rate of 10% per person-year), while none of the subjects identified as non-carriers of family variants developed disease (n=58). In subjects sub-grouped according to baseline-findings on ECG and echocardiography, relatives with abnormal (n=70) vs normal (n=268) findings had markedly higher incidence rates of FDC (overall 4.7% vs 0.4% per person-year), regardless of age-group (Figures 1 and 2). The relatives with abnormal ECG and/or echocardiographic findings at baseline had a (age-group-adjusted) hazard ratio of 12.9 (CI: 4.8 to 35.1, p<0.001), when compared to relatives with normal findings. Conclusion: Family screening identified a genetic predisposition to or overt FDC in 30% of screened relatives at baseline. In relatives not fulfilling criteria for FDC at baseline, findings from genetic testing and/or non-diagnostic findings on echocardiography and/or ECG were strongly associated with progression to disease. Importantly, relatives with normal genetic or objective findings had a low incidence rate and overall risk of developing FDC. Thus, baseline-screening identified a large proportion of relatives, in whom follow-up can be considered to be reduced allowing focused follow-up of relatives at higher risk of progression. Funding Acknowledgement: Type of funding sources: None.